FBXL13 directs the proteolysis of CEP192 to regulate centrosome homeostasis and cell migration - Fung, E; Richter, C; Yang, H; Schäffer, I; Fischer, R; Kessler, B; Bassermann, F; D'Angiolella, V (EMBO Press, 2018)
Aberrant centrosome organisation with ensuing alterations of microtubule nucleation capacity enables tumour cells to proliferate and invade despite increased genomic instability. CEP192 is a key factor in the initiation process of centrosome duplication and in the control of centrosome microtubule nucleation. However, regulatory means of CEP192 have remained unknown. Here, we report that FBXL13, a binding determinant of SCF (SKP1-CUL1-F-box)-family E3 ubiquitin ligases, is enriched at centrosomes and interacts with the centrosomal proteins Centrin-2, Centrin-3, CEP152 and CEP192. Among these, CEP192 is specifically targeted for proteasomal degradation by FBXL13. Accordingly, induced FBXL13 expression downregulates centrosomal γ-tubulin and disrupts centrosomal microtubule arrays. In addition, depletion of FBXL13 induces high levels of CEP192 and γ-tubulin at the centrosomes with the consequence of defects in cell motility. Together, we characterise FBXL13 as a novel regulator of microtubule nucleation activity and highlight a role in promoting cell motility with potential tumour-promoting implications.